Using fuzzy-technology for creation plan design works - Hladka, M. (Energy and Automation, 2015)
Described problems forming a plan of work in the implementation of the automated system. Successful implementation of the project requires a clear plan for the duration of each work project, but in the real world it is difficult to perform, because much depends not only on the performers, but also a large number of extraneous factors. So there is always uncertainty in the time duration of work within the development project plan. This leads to the need for Fuzzy-technologies for solving problems. This technology allows for various rankings (value) priority of work and, thus, is very effective in planning.